TEENAGER CADERIZATION TO RESPOND TO CARDIAC ARREST USING SMARTPHONE APPLICATION "BE ABYSTANDER" - Septi Dewi Rachmawati; Shila Wisnasari; Titin Andri Wihastuti; Rismawan Adi Yunanto; Dudella Desnani Firman Yasin (Caring : Jurnal Pengabdian Masyarakat, 2021)
Out-of-Hospital Cardiac Arrest (OHCA) is considered as a global health problem because of its high incidence and low survival rates. Cardiopulmonary Resuscitation (CPR) performed immediately by a bystander for OHCA patients increases the patients’ survival rate. However, the rate of CPR for OHCA patients remains very low due to the lack of willingness to become a bystander. One way to increase the number of CPR bystanders is by providing training on how to perform CPR. Students is considered to be the best bystander candidate because of their high curiosity and ability to memorize complex objects. This community service aims to increase the survival rates of OHCA patients through the youth cadreization responding to cardiac arrest using the Smartphone Application "Be A Bystander". This community service activity includes providing education about cardiac arrest and CPR, training on CPR with the simulation method (roleplay), and training on CPR using the “Be a Bystander” application. The indicators of the success of this community service are an increase in the knowledge, skills, and willingness of participants to become a bystander. Evaluation showed a significant increase in knowledge (p = 0.000), skills (p = 0.000), and willingness (p = 0.000) of participants before and after programs were carried out. After this community services activity, we hope more students are willing to become a competent bystander.